Prevalence of Myopic Maculopathy Among Adults in a Russian Population - Bikbov, Mukharram M; Gilmanshin, Timur R; Kazakbaeva, Gyulli M; Zainullin, Rinat M; Rakhimova, Ellina M; Rusakova, Iulia A; Bolshakova, Natalia I; Safiullina, Kamila R; Zaynetdinov, Artur F; Zinatullin, Ainur A; Nuriev, Ildar F; Khalimov, Timur A; et al. (JAMA Network Open, 2020)
IMPORTANCE: Although myopic maculopathy has become a major cause of vision impairment worldwide, few data from Russia and Central Asia on the prevalence of myopic maculopathy have been available. OBJECTIVE: To assess the prevalence of myopic maculopathy and its associations with ocular and systemic parameters in a population in Russia. DESIGN, SETTING, AND PARTICIPANTS: The Ural Eye and Medical Study, a population-based case-control study, was conducted in rural and urban areas in Bashkortostan, Russia, from October 26, 2015, to July 4, 2017. Data analysis was performed from September 13 to September 15, 2019. The Ural Eye and Medical Study included 5899 of 7328 eligible individuals (80.5%) aged 40 years or older. EXPOSURES: A detailed ocular and systemic examination included fundus photography and optic coherence tomography for the assessment of myopic maculopathy. MAIN OUTCOMES AND MEASURES: Prevalence of myopic maculopathy. RESULTS: The present investigation included 5794 of the 5899 eligible individuals (98.2%; 3277 [56.6%] women; mean [SD] age, 58.9 [10.7] years) with available information about myopic maculopathy. Mean (SD) axial length was 23.3 (1.1) mm (range, 19.78-32.87 mm). Prevalence of any myopic maculopathy was 1.3% (95% CI, 1.0%-1.6%); myopic maculopathy stage 2, 0.8% (95% CI, 0.6%-10.0%); stage 3, 0.2% (95% CI, 0.1%-0.4%); and stage 4, 0.2% (95% CI, 0.1%-0.4%). The prevalence of moderate to severe vision impairment and blindness was 29.8% (14 of 47 participants; 95% CI, 16.2%-43.3%) in stage 2 myopic maculopathy, 57.1% (8 of 14 participants; 95% CI, 27.5%-86.8%) in stage 3, and 100% (13 of 13 participants; 95% CI, 100%-100%) in stage 4. In multivariable analysis, a higher myopic maculopathy prevalence was associated with longer axial length (odds ratio [OR], 4.54; 95% CI, 3.48-5.92; P < .001), older age (OR, 1.04; 95% CI, 1.01-1.07; P = .03), and thinner peripapillary retinal nerve fiber layer thickness (OR, 0.96; 95% CI, 0.95-0.98; P < .001). After exclusion of glaucomatous eyes, the association between myopic maculopathy prevalence and thinner retinal nerve fiber layer remained significant (OR, 0.96; 95% CI, 0.95-0.98; P < .001). Myopic maculopathy prevalence was not significantly associated with sex; region of habitation; level of education; ethnicity; prevalence of arterial hypertension, chronic obstructive pulmonary disease, chronic kidney disease, diabetes, and inflammatory liver disease; hearing loss; depression score; or anxiety score. CONCLUSIONS AND RELEVANCE: In this ethnically mixed population from Russia, myopic maculopathy prevalence was mainly associated with elongated axial length and thinner peripapillary retinal nerve fiber layer, but was not associated with any major internal medical disease, level of education, ethnicity, or sex. Higher myopic maculopathy stage was associated with vision impairment and blindness. In addition to a known association between high axial myopia and glaucoma, myopic maculopathy may be associated with nonglaucomatous optic neuropathy.